Photoluminescent property of mechanically milled BaWO4 powder - Lima, R. C.; Anicete-Santos, M.; Orhan, E.; Maurera, M. A. M. A.; Souza, A. G.; Pizani, P. S.; Leite, E. R.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2007)
Crystalline BaWO4 (BWO) powder obtained by the polymeric precursor method was structurally disordered by means of high-energy mechanical milling. For the first time a strong and broad photoluminescence (PL) has been measured at room temperature for mechanically milled BWO powder and interpreted by ground-state quantum mechanical calculations in the density functional theory framework. Two periodic models have been studied; one representing the crystalline form and the other one representing the disordered BWO powder. These models allowed the calculation of electronic properties, which are consistent with the experimental results, showing that structural disorder in the lattice is an important condition to generate an intense and broad PL band. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: BaWO4; quantum mechanical; origin of photoluminescence; disorder effect